2022
DOI: 10.1182/blood.2021014698
|View full text |Cite
|
Sign up to set email alerts
|

PLAG1 dampens protein synthesis to promote human hematopoietic stem cell self-renewal

Abstract: Hematopoietic stem cell (HSC) dormancy is understood as supportive of HSC function and their long-term integrity. While regulation of stress responses incurred as a result of HSC activation is recognized as important in maintaining stem cell function, little is understood of the preventative machinery present in human HSCs that may serve to resist their activation and promote HSC self-renewal. We demonstrate that the transcription factor PLAG1 is essential for long-term HSC function and when overexpressed endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 110 publications
2
9
0
Order By: Relevance
“…Of these genes, the reduction in the zinc finger gene Plag1 is of significant interest as it has recently been demonstrated that PLAG1 regulates Msi2 expression (which is significantly downregulated at the RNA level in Cks2 −/− cells Figure 4F) 40 and PLAG1 is a proteostatic regulator in HSCs itself, important for maintaining low protein synthesis rates in HSCs. 41 The absence of a change in Foxo1 phosphorylation in Cks1 −/− cells compared with WT controls was surprising, but upon inspection of its key antioxidant transcriptional partner, NFκB, we found an analogous phenotype, with separation of total protein levels and phosphorylation status. Both Cks1 −/− and Cks2 −/− LT-HSCs had increased NFκB protein levels (Suppl.…”
Section: Transcriptomic Analysis Expands the Regulatory Network Of Ck...mentioning
confidence: 73%
See 1 more Smart Citation
“…Of these genes, the reduction in the zinc finger gene Plag1 is of significant interest as it has recently been demonstrated that PLAG1 regulates Msi2 expression (which is significantly downregulated at the RNA level in Cks2 −/− cells Figure 4F) 40 and PLAG1 is a proteostatic regulator in HSCs itself, important for maintaining low protein synthesis rates in HSCs. 41 The absence of a change in Foxo1 phosphorylation in Cks1 −/− cells compared with WT controls was surprising, but upon inspection of its key antioxidant transcriptional partner, NFκB, we found an analogous phenotype, with separation of total protein levels and phosphorylation status. Both Cks1 −/− and Cks2 −/− LT-HSCs had increased NFκB protein levels (Suppl.…”
Section: Transcriptomic Analysis Expands the Regulatory Network Of Ck...mentioning
confidence: 73%
“…Analysis of the individual genes comprising the Foxo1_01 GSEA module revealed 7 differentially expressed genes between Cks2 −/− LSK cells and WT controls (Figure 5G–L). Of these genes, the reduction in the zinc finger gene Plag1 is of significant interest as it has recently been demonstrated that PLAG1 regulates Msi2 expression (which is significantly downregulated at the RNA level in Cks2 −/− cells Figure 4F) 40 and PLAG1 is a proteostatic regulator in HSCs itself, important for maintaining low protein synthesis rates in HSCs 41 …”
Section: Resultsmentioning
confidence: 99%
“…Because it had been proven that IR-780 could enhance mouse HSCs repopulation capacity by raising the proportion of G0 HSCs, we tried to extend it to human CD34 + HSCs. Thus, we performed a transplantation assay to characterize the repopulation potential of human CD34 + HSCs (hHSCs) after IR-780 treatment in NOD-Prkdc scid Il2rg null (NSG) mice 38 . As shown in Figure 7, 1 × 10 4 human CD34 + hematopoietic cells with IR-780 treatment or not were transplanted with 6.25 × 10 3 mouse BM cells into recipient NSG mice after 3.15Gy irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Ex vivo activation in response to mitogenic stimuli has been also shown to affect additional HSC quality-control programs including mitochondrial metabolism, protein synthesis, autophagic recycling and UPR stress response early upon exposure to culture systems and prior to cell cycle progression 32,[81][82][83][84] . As we show that a stimulation time of approximately 16h is sufficient to affect the long-term repopulating potential of aged HSPC in transplantation experiments, one can speculate that the observed loss of aged HSC fitness may result from the combinatorial effects of dysregulated culture adaptation programs and the proliferative stress imposed by the transplant.…”
Section: Discussionmentioning
confidence: 99%